Evaluating Percutaneous Nephrolithotomy-Induced Kidney Damage by Measuring Urinary Concentrations of ?-2 Microglobulin - Sharifiaghdas, Farzaneh; Kashi, Amir Hossein; Eshratkhah, Ramin (Urology Journal, 2011)
Purpose: To assess percutaneous nephrolithotomy (PCNL)-induced kidney tubular damage and the associated factors. Materials and Methods: One hundred and eight patients who have undergone PCNL from May 2007 to October 2007 were recruited in this study. Urinary level of β2-microglobulin (Uβ2MG) was measured on the day before the operation as well as on the 1st, and 7th post PCNL days. Percutaneous nephrolithotomy was performed using standard method. Patients’ demographic and peri-operative data were collected to evaluate factors influencing renal injury. Results: Median urinary levels of β2-microglobulin on pre-operative, 1st, and 7th postoperative days were 0.2 mg/dL (range, 0.1 to 82), 0.4 mg/dL (range, 0.2 to 97), and 0.2 mg/dL (range, 0.2 to 114), respectively. High levels of Uβ2MG (> 2.3 mg/dL) were observed in 10 (9%), 20 (19%), and 10 (9%) patients pre-operatively and on the 1st, and 7th postoperative days, respectively. In multivariable analysis, Uβ2MG on the 1st postoperative day was associated with pre-operative serum creatinine level (P < .001) and diabetes mellitus (P = .05), while Uβ2MG on the 7th day after the operation was associated with pre-operative serum creatinine level (P = .01), diabetes mellitus (P = .01), and PCNL time (P = .02). Conclusion: Percutaneous nephrolithotomy does not cause kidney tubular injury beyond one week. In patients with pre-operative high serum creatinine concentration, diabetes mellitus, and/or long operation time, the likelihood of the kidney damage is higher than others.